The Neutron Halo Structure of 11Be and 14Be Nuclei Studied by the Binary Cluster Model - D Abdullah, Marwah; N Abdullah, Ahmed (Al-Nahrain Journal of Science, 2019)
We have calculated some of the basic structural properties such as the ground state proton, neutron and matter densities and elastic form factors of halo nuclei namely, 11Be and 14Be using the binary cluster model (BCM) within the Gaussian and harmonic oscillator wave functions. The halo nuclei have been considered as a compact core with loosely bound valence neutron(s) forming the halo. The comparison between the calculated and experimental matter density distributions supports the halo structure for 11Be [14Be] where the valence one neutron [two neutrons] occupy the 1p1/2 [(2s1/2)2] orbital. We have also calculated the reaction cross sections for these nuclei using the Glauber model with an optical limit approximation at low and high energies. The calculated of these nuclei give a good description of experimental data at both low and high energies.